Robust H∞ controller for high precision positioning system, design, analysis, and implementation - Raafat, Safanah M.; Akmeliawati, Rini; Abdulljabaar, Ismael (Scientific Research Publishing Inc., 2012)
In this paper, a systematic robust control design and analysis for a single axis precise positioner is presented. The effects of uncertainties on closed-loop stability and performance are considered in the H∞ robust controllers design. v-gap met- ric is utilized to validate the intelligently estimated uncertainty. The robust controllers are formulated within the frame- work of the standard H∞ mixed sensitivity optimization problem. Furthermore, a specially designed integral-H∞ and two-degree-of-freedom 2 DOF H∞ controllers are developed to provide improved robust performance and resolution properties. It is shown that the proposed design schemes are very effective for robust control and precise tracking per- formance of the servo positioning system.